THE IMPACT OF CURRENT GLOBAL CHANGES ON REGIONAL AND LOCAL ECONOMIES - MĂRGĂRITA ILINCA ANDRADA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
We are currently witnessing an increasingly accentuated dynamic of the globalization of the economy, an aspect that mainly generates the reduction of the importance of state borders, especially when we talk about trade or transfers of any kind. So, we identify an increasingly globalized economy, even if the specific institutions for a global policy are still missing. The benefits but also the costs of globalization are indisputable, they are often asymmetrically distributed, because they put poor people in poor countries at a disadvantage with serious consequences on the quality of life.